BUDIDAYA AYAM KAMPUNG INTENSIF MELALUI PROGRAM PENGEMBANGAN USAHA INOVASI KAMPUS - Sabar, Wara Pratitis; Riptanti, Erlyna Wida; Widyawati, Susi Dwi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2018)
The current native chicken commodity starts to show existence with the rise of culinary tourism in Indonesia. This provides a lucrative business opportunity for intensive native chicken farming. This article aims to cultivate intensive native chicken through the Campus Innovation Business Development Program.Patterns of intensive native chicken breeding is a method of raising livestock in cages by controlling feed and health so that livestock growth faster and maximum. This activity is done at Jatikuwung Experimental Farm, Animal Husbandry Program UNS with postal cage equipped with  niplee drinking, baby feder chick and hanging feeder.Results of native chicken farming activities begins males breeding with a ratio of 10: 1 and a cage size 2 m x 1 m to get a good quality eggs. The resulting eggs are then hatched and DOC (day old chick) will be kept as broiler chickens. Intensive chicken breeding has a shorter maintenance period of 2-3 months to achieve a weight of 1 kg. This result is much better than the cultivation of chicken with extensive.